2020
DOI: 10.1016/j.jmmm.2020.166655
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the skyrmion Hall effect in planar nanomagnets by the magnetic properties engineering: Skyrmion transport on nanotracks with magnetic strips

Abstract: Micromagnetic simulations have been performed to investigate the suppression of the skyrmion Hall effect in nanotracks with their magnetic properties strategically modified. In particular, we study two categories of magnetically modified nanotracks. One of them, repulsive edges have been inserted in the nanotrack and, in the other, an attractive strip has been placed exactly on the longest axis of the nanotrack. Attractive and repulsive interactions can be generated from the engineering of magnetic properties.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…In previous works, our group observed that the local decrease (increase) of the exchange stiffness constant acts as an attraction (repulsion) pinning center to a vortex, domain wall or skyrmion [33,34,41,42]. In two recent works [43,44] we showed other three ways to build magnetic skyrmion traps using magnetic defects, as variation in magnetocrystalline anisotropy, in DM interaction and in dipolar constant. Recently, we proposed several ways of suppression the skyrmion Hall effect in ferromagnetic nanotracks with their magnetic properties strategically modified [44].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In previous works, our group observed that the local decrease (increase) of the exchange stiffness constant acts as an attraction (repulsion) pinning center to a vortex, domain wall or skyrmion [33,34,41,42]. In two recent works [43,44] we showed other three ways to build magnetic skyrmion traps using magnetic defects, as variation in magnetocrystalline anisotropy, in DM interaction and in dipolar constant. Recently, we proposed several ways of suppression the skyrmion Hall effect in ferromagnetic nanotracks with their magnetic properties strategically modified [44].…”
Section: Introductionmentioning
confidence: 89%
“…Once Co/Pt multilayers allow the emergence of Néel-type skyrmions (hedgehog-type configuration), the magnetic configuration with a single skyrmion here been chosen as initial condition, by considering an analytical solution in which a Néel skyrmion is placed in a suitable position on the nanotrack. A description of the analytical model for skyrmions in nanotracks can be found in reference [44]. In the absence of a magnetic field or spin polarized current, the integration of the LLG equation leads to the stable configuration.…”
Section: Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is called skyrmion Hall effect (SHE) [20][21][22]. A number of proposals has appeared to bypass such an effect, for instance, the use of engineered materials [23,24], the substitution of skyrmions by other topological magnetic structures as information carriers [25], and the coupling of skyrmions in magnetic bilayers [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite many advantages associated with skyrmions, such as, enhanced stability due to its topological protection [8][9][10][11][12][13], ultra-low current density dynamics [14][15][16][17][18], and large Hall current [19,20], their transverse deflection upon application of current -known as skyrmion Hall effect -presents a major bottleneck for applications [21]. Therefore, reducing the transverse component of skyrmion velocity while retaining all of its favorable properties is an important goal of research in this field [22][23][24]. One of the approaches has been to tune the nature of the skyrmion state in such a way that the magnus force gets intrinsically canceled [25][26][27].…”
mentioning
confidence: 99%